Investigating the Predictive Value of Thyroid Hormone Levels for Stroke Prognosis - Aimilios Gkantzios; Vaia Karapepera; Dimitrios Tsiptsios; Eirini Liaptsi; Foteini Christidi; Elena Gkartzonika; Stella Karatzetzou; Christos Kokkotis; Mihail Kyrtsopoulos; Anna Tsiakiri; Paschalina Bebeletsi; Sofia Chaidemenou; et al. (MDPI AG, 2023)
Given the expansion of life expectancy, the aging of the population, and the anticipated rise in the number of stroke survivors in Europe with severe neurological consequences in the coming decades, stroke is becoming the most prevalent cause of functional disability. Therefore, the prognosis for a stroke must be timely and precise. Two databases (MEDLINE and Scopus) were searched to identify all relevant studies published between 1 January 2005 and 31 December 2022 that investigated the relationship between thyroid hormone levels and acute stroke severity, mortality, and post-hospital prognosis. Only full-text English-language articles were included. This review includes Thirty articles that were traced and incorporated into the present review. Emerging data regarding the potential predictive value of thyroid hormone levels suggests there may be a correlation between low T3 syndrome, subclinical hypothyroidism, and poor stroke outcome, especially in certain age groups. These findings may prove useful for rehabilitation and therapy planning in clinical practice. Serum thyroid hormone concentration measurement is a non-invasive, relatively harmless, and secure screening test that may be useful for this purpose.